State Security, “Slav-Bulgarian History” and Democracy in the 1990s: Nationalism and National Populism - Sirma Danova (Slavia Meridionalis, 2024)
State Security, Slav-Bulgarian History and Democracy in the 1990s: Nationalism and National Populism This case study is dedicated to the social implications provoked by the scandal surrounding the disclosure of Father Paisius of Hilendar’s illegal seizure of Slav-Bulgarian History (1762) – a milestone in the Bulgarian national identity – from Zograf Monastery on the Holy Mount of Athos in the 1990s, planned and realised by the State Security during the communist regime in Bulgaria. The object of the analysis is the populist discourse of former State Security agents, who held important public positions after the regime’s collapse and justified the seizure as a patriotic act. The focus of attention is the assertation of the nationalist historian Bozhidar Dimitrov. The second focus of the paper is the fetishisation of the story of Father Paisius at the National Historical Museum, which failed to prove its communicative value at a critical point in Bulgaria’s democracy.   Służby Bezpieczeństwa, Słowianobułgarska historia i demokracja lat 90. XX wieku. Nacjonalizm i narodowy populizm Artykuł stanowi studium przypadku poświęcone nielegalnemu przejęciu z klasztoru Zograf na Świętej Górze Athos rękopisu Słowianobułgarskiej historii (1762) św. Paisjusza z Hilendaru, a więc kamienia węgielnego bułgarskiej tożsamości narodowej. Przejęcie to zostało zaplanowane i zrealizowane w okresie reżimu komunistycznego przez bułgarskie Służby Bezpieczeństwa. Artykuł podejmuje również kwestie implikacji społecznych, wywołanych skandalem związanym z ujawnieniem tej sprawy w latach 90. XX wieku. Przedmiotem analizy jest dyskurs populistyczny byłych agentów Służby Bezpieczeństwa, którzy po upadku reżimu zajmowali ważne stanowiska publiczne, a przejęcie rękopisu uzasadniali jako akt patriotyczny. W centrum uwagi znajdują się twierdzenia nacjonalistycznego historyka Bożydara Dimitrova, a także fetyszyzacja narracji o św. Paisjusza z Hilendaru w Narodowym Muzeum Historycznym w Sofii, która w krytycznym momencie bułgarskiej demokracji nie zdołała wykazać swojej wartości komunikacyjnej.